Children’s Views About Their Future Career and Family Involvement: Associations With Children’s Gender Schemas and Parents’ Involvement in Work and Family Roles - Endendijk, Joyce J.; Portengen, Christel M. (Frontiers in Psychology, 2022)
Substantial gender disparities in career advancement are still apparent, for instance in the gender pay gap, the overrepresentation of women in part-time work, and the underrepresentation of women in managerial positions. Regarding the developmental origins of these gender disparities, the current study examined whether children’s aspirations and expectations about future career and family involvement were associated with children’s own gender cognitions and parents’ career- and family-related gender roles. Participants were 142 Dutch families with a child between the ages of 6 and 12 years old (M = 9.80, SD = 1.48, 60% girls). The families had different compositions (1 parent, 2 parents, 1 to 3 children). Children completed a computer task assessing gender stereotypes about toys and questionnaires on gender identity (i.e., felt similarity to same- and other-gender children) and their aspirations and expectations for future career and family involvement. Parents reported their occupation, work hours, and task division in the home, which were combined in a composite variable reflecting gender-typicality of career and family involvement. Generalized estimation equations were used to take into account dependency between family members. Results revealed that parents’, and especially mothers’, gender-typical career and family involvement was associated with children’s gender-typical career and family aspirations and expectations. In addition, children’s felt similarity to the same gender was associated with children’s gender-typical career and family expectations. These findings suggest that parents’ career, work hours, and task division in the home, play an important role in how their children envision their future work and family roles. Children themselves also play an active role in developing this vision for the future by their own gender identity, specifically by how similar they feel to individuals of the same gender. To reduce gender disparities in the occupational and domestic domain, programs need to be designed that focus on parental role modeling in the family as well as children’s gender identity development.